The role of gabapentinoids in acute and chronic pain after surgery. Issue 5 (October 2019) - Kumar, Amanda H.; Habib, Ashraf S.
Abstract : Purpose of review: Gabapentinoid use has increased substantially in the past several years after initial promising data with regard to acute perioperative pain control. The purpose of this review is to critically appraise the evidence for the use of gabapentinoids for acute pain management and its impact on the development of chronic pain after surgery. Recent findings: Recent meta-analyses have revealed that prior data likely have overestimated the beneficial effects of gabapentinoids in acute perioperative pain while underestimating the associated adverse effects. The utility of gabapentinoids in the setting of enhanced recovery pathways and for the prevention of chronic postsurgical pain is still unclear. Moreover, there has been increasing concern regarding the potential for misuse and abuse of gabapentinoids. Summary: Current evidence does not support the routine use of gabapentinoids as part of a multimodal analgesic regimen in enhanced recovery pathways. We recommend being selective with regard to using gabapentinoids for acute postoperative pain management after careful consideration of the potential side effect profile based on patient comorbidities as well as the expected severity of postoperative pain. Large, high-quality trials are needed to identify the impact of gabapentinoids in the context of multimodal anagelsia.